2005
DOI: 10.1038/sj.jhh.1001815
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of QT-interval parameters for cardiovascular risk stratification in type 2 diabetic patients with arterial hypertension

Abstract: QT-interval parameters are potential indicators of increased cardiovascular risk. We evaluated prospectively their prognostic value, in relation to other risk markers, for cardiovascular fatal and nonfatal events in a cohort of 271 hypertensive type 2 diabetic outpatients. QT intervals were measured from 12-lead standard ECGs obtained on admission and maximum rate-corrected QTinterval duration and QT-interval dispersion (QTd) calculated. Clinical and laboratory data and 2-D echocardiograms (available in 126 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Also, a prolonged QTc interval is thought to provide additional prognostic information for cardiovascular morbidity and mortality rates beyond that obtained from conventional risk markers in type 2 diabetic patients with hypertension [29]. Spironolactone therapy, in our study, resulted in a significant reduction in QTc intervals compared with placebo.…”
Section: Discussionmentioning
confidence: 50%
“…Also, a prolonged QTc interval is thought to provide additional prognostic information for cardiovascular morbidity and mortality rates beyond that obtained from conventional risk markers in type 2 diabetic patients with hypertension [29]. Spironolactone therapy, in our study, resulted in a significant reduction in QTc intervals compared with placebo.…”
Section: Discussionmentioning
confidence: 50%
“…Increased QTd is another indicator of myocardial electrical instability that has been associated with arrhythmias and cardiac death (18). In general medical populations, QTd is an independent predictor of cardiovascular mortality (hazard ratio 1.28 [95% CI 1.01, 1.60] per each 10-msec increase in QTd) (19). In patients with rheumatic diseases, a 50-msec increase in the QTc interval has been associated with a doubling of the relative hazard for all-cause mortality, and some authors have suggested a connection between disease activity and arrhythmogenesis (20).…”
Section: Discussionmentioning
confidence: 99%
“…Also, experimentally, regression of LVH normalizes LVH-induced proarrhythmic repolarization abnormalities, 28,30 whereas reduction in LVM and regression of electrocardiographic LVH indexes are associated with QT interval shortening. 31 Finally, it was demonstrated recently that QT parameters are predictors of cardiovascular mortality in hypertensive patients with electrocardiographic LVH 10 and with type 2 diabetes, 11 as it was already known for electrocardiographic indexes of LVH. 32,33 Therefore, it appears reasonable to speculate that QT interval parameters and ECG voltage indexes could act in combination not only to determine an increased chance of having echocardiographic LVH, but also to identify a subgroup of hypertensive patients with a high cardiovascular risk profile, particularly for sudden arrhythmic death.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been reported recently that they probably constitute true cardiovascular mortality markers in hypertensive patients. 10,11 As far as we know, no study has evaluated QT interval parameters in patients with RH, a common but generally understudied subgroup of hypertensive patients.Therefore, the objective of this study was to assess the relationships between various QT interval-derived parameters and echocardiographic LVH in a large group of RH patients and, particularly, to evaluate whether any QT parameter can provide additive information for LVH detection beyond that obtained from the best ECG voltage criterion. …”
mentioning
confidence: 99%
See 1 more Smart Citation